Transcription regulators and ultra-rare and other rare translocation-related sarcomas treated with trabectedin: A proof of principle from a post-hoc analysis - Palmerini, Emanuela; Sanfilippo, Roberta; Grignani, Giovanni; Buonadonna, Angela; Romanini, Antonella; Badalamenti, Giuseppe; Ferraresi, Virginia; Vincenzi, Bruno; Comandone, Alessandro; Pizzolorusso, Antonio; Brunello, Antonella; Gelsomino, Fabio; et al. (Frontiers in Oncology, 2022)
Background: Among sarcomas, which are rare cancers with an incidence of <6 per 100.000/year cases, ultra-rare sarcomas have an incidence of approximately ≤1/1,000,000/year cases and altogether account for ~20% of all soft tissue sarcomas (STS) and bone sarcomas. The Italian Sarcoma Group has recently performed a non-interventional, retrospective TrObs study with data from 512 anthracycline-pretreated patients with advanced multiple STS histologies and treated with trabectedin (Palmerini, Cancers 2021; ClinicalTrials.gov Identifier: NCT02793050). Methods: A post-hoc analysis of case series to evaluate the efficacy and safety of trabectedin on patients with ultra-rare and other rare translocation-related sarcomas included in TrObs study was performed. Main outcomes comprised investigator-assessed overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS) and safety. Results: Thirty-six patients (18 women) with ultra-rare and other rare sarcoma and a median age of 53.0 years (range: 22-81) were included. Most patients had solitary fibrous tumor (SFT; n=11) followed by epithelioid sarcoma (n=5), malignant peripheral nerve sheath tumor (MPNST; n=4), extraskeletal myxoid chondrosarcoma (EMC; n=3) and desmoplastic small round cell tumor (DSRCT; n=3), and alveolar soft part sarcoma (ASPS), rhabdomyosarcoma and clear cell sarcoma (n=2 each). Thirty-five patients had metastatic disease and 23 patients received trabectedin as a second-line treatment. Among 35 patients evaluable for response, two patients with SFT and ASPS had a partial response and one patient with DSRCT obtained a complete response, reaching an ORR of 8.6% (95% CI: 2.8-23.4%). Among patients with an ORR, 6-months PFS was 100% in patients with ASPS, 45.7% in patients with SFT and 33.3% in those with DSRCT. Two patients with epithelioid sarcoma and myoepithelioma had disease stabilization lasting >24 months. Nine patients had at least one grade 3/4 adverse event, mostly being bone marrow toxicity (n=6). Conclusions: Trabectedin has some anti-tumor activity in some ultra-rare and other rare sarcomas, particularly translocation-related sarcomas, with the well-known manageable safety profile.